2015
DOI: 10.3109/14767058.2015.1086743
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the pre-pregnancy weight of the mother and the gestational weight gain on the bilirubin level of term newborn

Abstract: We conclude that the babies with mothers who gained more weight than the advised amount were under risk for newborn jaundice. Therefore, these babies should be monitored more closely for neonatal jaundice and prolonged jaundice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“… 17 Another study by Özdek et al demonstrated that mothers who have more weight than the advised amount may be at risk of neonatal jaundice. 18 Conversely, many studies have reported that this variable was not correlated with hyperbilirubinemia. 19 , 20 In the present study, the mean age of mothers in patients was determined as 28.8 years (Maximum: 43 years; Minimum: 17 years).…”
Section: Resultsmentioning
confidence: 98%
“… 17 Another study by Özdek et al demonstrated that mothers who have more weight than the advised amount may be at risk of neonatal jaundice. 18 Conversely, many studies have reported that this variable was not correlated with hyperbilirubinemia. 19 , 20 In the present study, the mean age of mothers in patients was determined as 28.8 years (Maximum: 43 years; Minimum: 17 years).…”
Section: Resultsmentioning
confidence: 98%
“…Studies were published from 2009 to 2017 [ 5 , 28 89 ]. The population recruitment periods were 1 year in 12 studies [ 28 , 34 , 35 , 39 , 41 , 50 , 53 , 58 , 59 , 67 , 85 , 86 ], 2 years in 15 studies [ 30 , 33 , 36 , 37 , 40 , 54 56 , 60 , 74 , 83 , 84 , 87 89 ] and more than 2 years in 36 studies [ 5 , 29 , 31 , 32 , 38 , 42 49 , 51 , 52 , 57 , 61 66 , 68 – 73 , 75 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…The mean maternal age ranged from 23.6 to 33.0 years. Preterm delivery rates were reported by 40 studies ranging from 0.0 to 21.34% (Table 1 ) [ 28 , 29 , 31 35 , 37 , 39 42 , 46 , 47 , 49 , 51 , 52 , 54 56 , 59 , 60 , 62 , 63 , 65 67 , 69 , 70 , 72 , 73 , 76 , 77 , 79 82 , 84 , 88 , 89 ]. Twenty studies did not report the mean BMI [ 30 , 31 , 33 , 35 , 36 , 38 , 41 , 42 , 55 , 58 , 61 , 70 72 , 74 , 78 , 80 , 82 , 83 , 88 ] and only two studies did not report the prevalence of BMI categories [ 48 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk factors for the development of prolonged jaundice in newborns are complications during pregnancy and childbirth, the presence of gynecological and extragenital pathology in mothers , and onerous obstetric history, as well as prematurity, asphyxia, and cerebral ischemia [20][21][22]. The maternal age, weight, body mass index (BMI), numbers of pregnancies and prolonged delivery were significantly associated with bilirubin levels [23][24][25].…”
Section: Characteristicsmentioning
confidence: 99%